2022
DOI: 10.1371/journal.pone.0268033
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of combined oral sucrose and nonnutritive sucking in pain management for infants: A systematic review and meta-analysis

Abstract: Background Pain management is currently important in neonatal intensive care unit (NICU). The superiority in pain relief of the combined oral sucrose (OS) and nonnutritive sucking (NNS) to other single intervention has not been well established. The administration of sucrose has been considered to potentially induce adverse events, which has been controversial. This study aims to investigate the combined effects and safety in comparison with other single intervention methods, including NNS, OS alone, breast mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Non-nutritive and or sucrose/glucose suckling are well studied and established methods that are helpful [ 98 ] albeit for mild pain [ 94 ]. Breastfeeding especially direct, has been found to be the best practice in non-pharmacological pain management [ 61 ], compared all other methods [ 76 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-nutritive and or sucrose/glucose suckling are well studied and established methods that are helpful [ 98 ] albeit for mild pain [ 94 ]. Breastfeeding especially direct, has been found to be the best practice in non-pharmacological pain management [ 61 ], compared all other methods [ 76 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…NNS is considered a safe and effective method of pain relief during the pinprick procedure in neonates [ 71 ]. But it is more effective in conjunction with sucrose/glucose sucking [ 94 ]. A randomized controlled clinical trial with cross-over design [ 97 ] in an Iranian NICU with 60 infants demonstrated the effectiveness of using oral dextrose for pain management during a heel prick in comparison to facilitated tucking.…”
Section: Non-pharmacological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the published studies on the impact of frenulotomy take into account the fact that sucking and feeding are soothing to infants and as such, the observed improvements immediately following frenulotomy may be a response to the pain associated with the procedure rather than a result of the procedure itself ( 42 , 43 ). It has been shown that non-nutritive sucking attenuates the pain associated with circumcision ( 43 ) and in the author's experience, infants feed vigorously immediately after circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a subset of 5399 babies on the type of procedure associated with sucrose administration or whether complementary NNS were also explored. NNS has been shown, in a recent systematic review, to complement sucrose resulting in lower pain intensity outcomes 10 . Using this combination of strategies to reduce pain during the entire NICU stay and their effect of outcomes requires further investigation.…”
Section: Discussionmentioning
confidence: 99%